La Limitación que impone la Ley Orgánica de Garantías Jurisdiccionales y Control Constitucional Respecto de los Recursos Administrativos como Requisito para la Interposición de la Acción de Protección - García Encalada, Víctor Xavier (2016)
Performing an analysis of the problems that are occurring in our society, I observed that at present a large number of protective action are rejected because the administrators of justice being based on the Organic Law of Guarantees Jurisdictions and Constitutional Control exists, in paragraphs 3 of Article Art. 40, which states as a condition for bringing the action of the protection. "3 Absence of other adequate legal defense mechanism. ", And in paragraph 4 of Article 42 of the law in question before ,, which provides:" 4. When the administrative act can be challenged in court, except via a showing that the path be not appropriate or effective "; This action goes against the provisions of Art. 88 of the Constitution of the Republic of Ecuador in which it is established that the protective action shall relate to the direct and effective protection of the rights recognized in the Constitution, and may filed when there is a violation of constitutional rights. If the protection action seeks to protect a right before it is breached, it is absurd to demonstrate that the administrative act can not be contested in the courts, until this situation arises, is to find the right at risk of being violated In Article 10 paragraph 8, paragraph two of the Organic Law of Guarantees Jurisdictions and Constitutional Control points out that in case of not meeting the demand the necessary requirements, providing that it is completed within a period of three days, after this term, if the demand is incomplete and the story follows that there is a serious violation of rights, the judge must deal with it and rectify the omission of the requirements within its power to appropriate audiences. In this situation it is in breach of the provisions of our constitution, because the provisions of simplicity, speed and efficiency, does not apply must be taken into account as set out in the law in question, it states that it is not necessary sponsorship a lawyer, and therefore should be granted facilities for it to be filed, the term established three days, is absurd, because eventually if not completed will continue to trade, as well as can be done from Initially The purpose of the action is to forewarn protection or repair the constitutional rights that have been or may be subject to infringement, this requires that such action is applied quickly and effectively